2021
DOI: 10.1097/mbp.0000000000000560
|View full text |Cite
|
Sign up to set email alerts
|

Could the systemic immune-inflammation index be a predictor to estimate cerebrovascular events in hypertensive patients?

Abstract: Background and objectives Hypertension is one of the most important risk factors for cardiovascular and cerebrovascular events. Inflammatory processes occupy an important place in the pathogenesis of hypertension. Many studies have studied inflammatory markers responsible for the onset of hypertension and organ damage. In this study, we investigated whether the systemic immune-inflammation index (SII) (platelet × neutrophil/lymphocyte), -one of the new inflammatory markers -can be used to predict cerebrovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Of the 152,996 participants, 102,822 were male and the mean/median age ranged from 33 to 70 years. The published studies were conducted in four regions: China ( 28 , 29 , 31 , 32 , 34 , 35 , 39 , 40 ), Turkey ( 30 , 33 , 38 ), Poland ( 36 ), and United States ( 37 ). The determination of SII cutoff values was based on ROC analysis, Youden index, and quartiles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 152,996 participants, 102,822 were male and the mean/median age ranged from 33 to 70 years. The published studies were conducted in four regions: China ( 28 , 29 , 31 , 32 , 34 , 35 , 39 , 40 ), Turkey ( 30 , 33 , 38 ), Poland ( 36 ), and United States ( 37 ). The determination of SII cutoff values was based on ROC analysis, Youden index, and quartiles.…”
Section: Resultsmentioning
confidence: 99%
“…Except for cerebral small vessel disease (HR = 1.09, 95%CI: 0.95-1.25, P = 0.233), coronary heart disease (HR = 1.13, 95%CI: 0.94-1.36, P = 0.188), and venous thrombosis (HR = 4.65, 95%CI: 0.66-32.71, P = 0.122), there was a consistent statistical significance for the risk of ischemic stroke (HR = 1.31, 95%CI: 1.06-1.63, P = 0.013), hemorrhagic stroke (HR = 1.22, 95%CI: 1.10-1.37, P < 0.001), myocardial infarction (HR = 1.11, 95%CI: 1.01-1.23, P = 0.027), and peripheral arterial disease (HR = 1.51, 95%CI: 1.18-1.93, P = 0.001) (Table 2). Furthermore, nine studies reported differences in SII levels at the onset of CVD compared with the general population (28,30,(32)(33)(34)(36)(37)(38)(39), and all studies consistently suggested that SII levels at the onset of CVD were significantly higher than that in controls, with a median elevation range of 12-1,340. The random-effects model was used due to substantial heterogeneity (I 2 = 99.7%, P < 0.001), and the pooled WMD was 355.2 (95% CI: 234.8-475.6, P < 0.001) (Figure 2B), further confirming the correlation between SII and CVD development.…”
Section: Association Between Systemic Immune-inflammation Index and C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The association between SII and SIRI at baseline and risk of CVD had been previously examined. [33][34][35] For example, Aydin et al found that higher SII level would increase the risk of stroke. 33 Jin et al concluded that higher SII and SIRI were associated with higher risk of developing CVD during a median follow-up period of 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic immune-inflammation index (SII), a new type of inflammatory index, is calculated by combining three immune inflammatory cells—lymphocytes, neutrophils, and platelets—and fully reflects the inflammation status ( 16 ). A high SII level increases the risk of stroke in patients with hypertension and affects patients' prognosis ( 17 ). Therefore, the purpose of our study was to calculate the SII according to the first routine blood test at admission, construct a model for the prediction of DC requirements, and verify the predictive value of the SII to provide a tool for the selection of DC in patients with LAO-AIS after MT.…”
Section: Introductionmentioning
confidence: 99%